A Study on the Impact of a Short Training Course on the Management of Artificial Intelligence-Assisted Learning at SMK Nusatama Kota Padang - Septy, Adzanil Prima; Tavriyanti, Lisa; Husna, Lailatul (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Given the rapid advancements in information and communication technology, particularly in artificial intelligence (AI), this study explored the impact of a short training course on the management of AI-assisted learning at SMK Nusatama in Padang city conducted in the mids of August 2024. Designed to enhance teachers' competencies in integrating technology into the learning process, the study emphasized the methodology used to assess improvements in teachers' services and understanding. A set of questionnaires was administered to gauge the potential of AI in teaching. The findings revealed that the training effectively improved teachers' ability to incorporate AI into their teaching methods, enrich instructional materials, and foster student interaction and assessment. Additionally, the training played a significant role in developing teachers' digital skills, which were essential for navigating the challenges of education in the digital era. These findings were expected to serve as a valuable reference for further development in the application of AI within educational settings, particularly in vocational schools.